The influence of colors in work and trade settings: Complementary colors, mood states and retail environment - Martinez, Luisa Margarida Guerra Marques (My University, 2019)
This thesis seeks to discuss the influence of color in work and trade settings, to assess the implications of their applicability in both organizational behavior and retail environment. This investigation was sprung with a preliminary literature review about the influence of space and color in organizational behavior. Subsequently, our major research queries were outlined and three focal studies following a within-subject design about color thus ensued. We first sought to understand the emotional processes behind the choice of complementary colors. Bearing in mind that the literature about complementary colors and emotions is scarce, we analyzed the association between complementary colors and mood states (Chapter I). Through an experimental study, 39 participants were instructed to choose colored cards at four different moments through time, after the induction of an emotional state. Four emotion conditions were evoked by means of autobiographical recall (i.e., happiness, sadness, balanced mood, unbalanced mood). Findings showed that complementary colors were preferred in the unbalanced mood scenario, suggesting that the color choice might rely on partially conscious mechanisms aiming at regaining a balanced state. Secondly, we investigated the interrelation between anthropomorphic packaging and color choices (Chapter II). A total of 259 participants were exposed to non-anthropomorphic and anthropomorphic packaging, considering a product from the real market (Milaneza pasta). Four different color conditions were rated in terms of attractiveness and purchase intention. Our findings suggested that anthropomorphism influenced product’s attractiveness but did not affect purchase intention. Importantly, the green anthropomorphic package produced an almost complementary color contrast between the pasta and the package (vivid green vs. orange-red), leading to a higher color contrast perception that positively affected the product’s attractiveness. In the third study, 436 participants assessed two retail scenarios – orange store and blue store – and two products – chocolate and soap (Chapter III). The products varied in color (red, orange, blue and beige), and were assessed in both stand-alone and embedded in the store situations, through image manipulation. Our results showed that there was a triple interaction resulting from retail environment color × product color × product category. Accordingly, we reinforce the idea that color should not be considered individually, but always in the context where it is inserted. With these three studies, we aim to contribute to the knowledge about the influence of color in human behavior. Crucially, we validate our prediction concerning the presumed effect of complementary colors, both emotionally and in retail settings. Here, we discuss the theoretical and practical implications of these findings.

Nesta tese pretendemos discutir a influência da cor no comportamento organizacional e em contexto de marketing, assim como a aplicabilidade deste conhecimento. A investigação teve início com uma revisão de literatura acerca da influência do espaço e da cor no comportamento organizacional. De seguida, o nosso trabalho começou a delinear-se com maior definição, e foram desenvolvidos três estudos sobre cor, com design intra-sujeitos. Em primeiro lugar, tivemos como objetivo o entendimento sobre os processos emocionais que desencadeiam a escolha de cores complementares. Tendo em conta que a literatura sobre cores complementares e emoções é escassa, analisámos a associação entre cores complementares e estados emocionais (Capítulo I). Através de um estudo experimental intra-sujeitos, 39 participantes escolheram cartões coloridos em quatro momentos diferentes, depois da indução de um estado emocional. Foram induzidas quatro condições emocionais (i.e., felicidade, tristeza, equilíbrio emocional, desequilíbrio emocional) através da redação de um episódio autobiográfico. Os resultados revelaram que os cartões que apresentavam as cores complementares foram preferidos quando o desequilíbrio emocional foi evocado, sugerindo que a escolha de cores pode estar baseada em mecanismos psicológicos parcialmente conscientes, procurando de forma inconsciente recuperar um estado emocional mais equilibrado. Em segundo lugar, investigámos a inter-relação entre embalagens antropomórficas e escolhas de cores (Capítulo II). Um total de 259 participantes escolheram entre embalagens antropomórficas e não antropomórficas, considerando um produto existente no mercado (massa Milaneza). Foram avaliadas quatro cores diferentes em termos de atratividade do produto e intenção de compra. Os resultados mostraram que o antropomorfismo beneficia a atratividade do produto, mas não afeta a intenção de compra. Adicionalmente, a embalagem antropomórfica de cor verde produziu um contraste entre cores quase complementares entre si (verde vívido vs. laranja avermelhado), considerando a massa e a embalagem. Este maior contraste entre cores terá produzido uma perceção que afetou positivamente a atratividade do produto. No último estudo, 436 participantes compararam imagens de dois ambientes de loja – loja laranja e loja azul – e dois produtos – chocolate e sabão (Capítulo III). Os produtos analisados divergiam apenas na cor (vermelho, laranja, azul e bege) e foram avaliados de duas formas: (i) individualmente; e (ii) adicionados ao ambiente de loja através de manipulação digital da imagem. Os resultados demonstraram que houve uma tripla interação resultante do ambiente de loja × produto × categoria de produto. Validámos a ideia de que a cor não deve ser considerada individualmente, mas sempre no contexto onde está inserida. Com estes estudos, pretendemos contribuir para o conhecimento sobre a influência da cor no comportamento humano. O presumido efeito produzido pelas cores complementares, decorrente de fatores emocionais e de perceção, foi validado através da nossa investigação. Por último, implicações teóricas e práticas acerca destes resultados são discutidas.
Keywords: Color; Complementary colors; Workspace; Mood States; Organizational behavior; Attractiveness; Purchase intention; Packaging; Retail environment